Mutu dan Kesukaan Konsumen terhadap Mie Basah Berbahan Dasar Tepung Ganyong dan Tepung Terigu pada Berbagai Taraf Perlakuan - Martha Syiviana Sari, Dwi Agustiyah Rosida, Gatot Sargiman Richardus Widodo (AGROKNOW, 2013)
Abstract. The study examines the utilization of âganyongâ and wheat flour to make wet noodle by testing the quality and consumerâs preference. The use of âganyongâ flour as ingredient to make wet noodle is expected to diversify canna-based products and to reduce wheat imports.Â The method used is experimental study by applying Random Block Design (RBD) 1 factor that is the combination between wheat flour and âganyongâ flour with 3 levels. G1 is a 10% âganyongâ flour and a 90% wheat flour, G2 is a 20% âganyongâ starch and a 80% wheat flour, and G3 is a 30% âganyongâ flour and a 70% wheat flour. The collected data are analyzed by variance analysis and LSD (Least Significant Difference) test if there is no real difference.From the assessment of quality (chemical test results), it shows that the combination of âganyongâ and wheat flour to make wet noodles shows significant effect differences on the moisture and protein contents (P< 0,05) in which the higher water content, the lower the level of protein produced. There is no significant effect differences for ash content (P>0,05). From the consumerâs preferences, it shows that most consumers do not like its color, taste, and suppleness. To increase consumerâs preferences of wet noodle made from wheat and âganyongâ flour, it is suggested to add gluten or artificial alkali salt to improve firmness. It also needs to soak âganyongâ in sodium metabisulfite powder to get brighter color.Kata Kunci : Mie basah, tepung ganyongÂ